CASE STUDY OF 1ST STAGE ACTIVE PHASE OF LABOR WITH CONTRACTION PAIN USING NON - PHARMACOLOGICAL THERAPY IN THE WATERSHED AREA (DAS) OF PALANGKA RAYA CITY (Proceedings OPTIMAL, 2024)
Background: Childbirth is the process of expelling a fetus that occurs at term (37-42 weeks) and is born spontaneously with a posterior presentation without complications for the mother and fetus. Childbirth is a normal physiological event. The Childbirth is a social event for mothers and families to look forward to for 9 months. During birthing process, the mother feels pain which can disrupt comfort during contractions, and can affect psychological conditions and cause complications during the birth process Objectives: Providing Midwifery and Childbirth Care to Mrs. S G2P1A0 Age 27 Years Old during 1st Active Phase with Contraction Pain At UPTD Pahandut Community Health Center. Method: The type of research used is descriptive qualitative with a case study approach method. The design uses field observations. Data collection methods include interviews and analysis of midwifery care documentation. Data analysis was obtained from case study research by creating a narrative from the results of observations and descriptions of midwifery care analysis, assessment, formulating diagnoses, planning, implementing and evaluating midwifery care. The research was conducted in June 2024. Results: Mrs. S was willing to try alternative complementary medicine, using the Birthing Ball (Pilates ball) by doing movements such as sitting on the ball and rocking back and forth, and the mother felt that the pain relieved and more comfortable.